The Spanish project on alternatives to methyl bromide (2): The case of strawberry in the area of Valencia - Bartual, Rafael; Cebolla, Vicent; Bustos, Julia; Giner, Alfonso; López-Aranda, José M. (2017)
Among the possible alternatives to methyl bromide (MB) are physical and chemical methods including the recovery of old ones, combinations among them, or solarization. To consider alternatives to MB, it is necessary to examine long-term effects and the feasibility of repeating the treatment in the same field several years consecutively, without losses in yield and fruit quality. Seven treatments were included. in the experiment: non treated control; standard dosage application of MB (60g/m(2)), half dosage application of MB (30g/m(2)) using VIF tarp; moderate rates of manure (5kg/m(2)) combined with solarization; reduced dosages of Metham-Na (35g/m(2)) combined with solarization; Metham-Na at standard dosages (140g/m(2)); and fresh manure at high rates (15kg/m(2)). After two years of research, we can foresee that improved solarization with manure offers the better possible alternative especially in the case of small farms. For such farms, manure supplies in Valencia are available and its application is feasible from the economic stand point of view. Meanwhile, VIF treatment is the only immediate alternative for all the variables under study until the phase out of MB in 2005.